(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The article describes the formation of the revenue base of local budgets, the importance of land tax and property tax, and the scientific and practical basis. The possibilities of ensuring the stability of local budgets’ incomes are based. Procedures and practical recommendations were offered to increase the importance of land and property tax in the formation of local budget revenues. In addition, a study was conducted on ways to increase local budget revenues, studies of economists were studied within the scope of the topic, and conclusions and proposals were formed.